2021
DOI: 10.1002/jts.22752
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the associations between childhood trauma and cardiovascular health in midlife

Abstract: Growing evidence suggests that childhood trauma is associated with poorer cardiovascular health in adulthood, but few studies have examined potential mediators of these associations. We examined the links between different forms of childhood trauma (i.e., abuse, neglect, cumulative trauma) and cardiovascular health and explored potential mediators. Cross‐sectional data from 1,251 participants in the National Survey of Midlife Development in the United States’ II Biomarker Project were analyzed. Path analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…To our knowledge, only one prior study has examined the influence of any form of trauma on LS7 scores in any population. Using data from the Midlife in the United States (MIDUS) Study, investigators found that a greater severity of childhood trauma (i.e., abuse and neglect) was associated with worse CVH (measured using LS7) in a multiethnic sample of middle-aged and older adults (Caceres et al, in press). Our findings are consistent with the findings of that study (Caceres et al, in press), but instead of only examining childhood trauma, we assessed trauma exposure across the life span.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one prior study has examined the influence of any form of trauma on LS7 scores in any population. Using data from the Midlife in the United States (MIDUS) Study, investigators found that a greater severity of childhood trauma (i.e., abuse and neglect) was associated with worse CVH (measured using LS7) in a multiethnic sample of middle-aged and older adults (Caceres et al, in press). Our findings are consistent with the findings of that study (Caceres et al, in press), but instead of only examining childhood trauma, we assessed trauma exposure across the life span.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Midlife in the United States (MIDUS) Study, investigators found that a greater severity of childhood trauma (i.e., abuse and neglect) was associated with worse CVH (measured using LS7) in a multiethnic sample of middle-aged and older adults (Caceres et al, in press). Our findings are consistent with the findings of that study (Caceres et al, in press), but instead of only examining childhood trauma, we assessed trauma exposure across the life span. As most research on trauma and CVH in Latinas has focused on childhood abuse, our findings contribute to a limited body of literature on the associations of exposure to trauma across the life course with CVH in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that for every 1-unit increase in Risky Family score, the odds of attaining high CVH (≥10) decreased by 3.6% (odds ratio, 0.9645 [95% CI, 0.94-0.98]). This study adds to a series of work 7,8 identifying the role of childhood adversity in influencing modifiable risk factors for cardiovascular disease. It expands the conceptualization of adversity by considering the frequency of experiences, which has not always been considered in prior work.…”
Section: See Article By Ortiz Et Almentioning
confidence: 99%
“…9 For example, work with the National Survey of Midlife Development in the United States has shown depressive symptoms to mediate associations between childhood trauma and cardiovascular health. 7 Behavioral factors such as sleep quality and quantity have also been associated with childhood adversity, as well as mediated the association between adversities and cardiovascular health. 7 In fact, sleep is now the eighth component of American Heart Association’s cardiovascular health metric, given its importance in the development of cardiovascular disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation